Research on intelligent analysis device for dynamic error of electric energy - Wenjing Yang; Gang Wang; Wei Gao; Jingyu Yin; Weitao Wu (AIP Advances, 2024)
With the development of smart grids, the introduction of intermittent energy and the increase in dynamic loads have led to more and more dynamic characteristics of electricity loads in the grid. Intelligent energy meters that passed calibration under steady-state load may not necessarily meet the measurement error requirements under the excitation of dynamic load test signals, and some may even produce significant errors. At present, research on dynamic error testing of intelligent energy meters mainly focuses on establishing models of dynamic error testing signals, and the reasons for the generation of dynamic errors are still unclear. In order to analyze the sources of dynamic errors in intelligent energy meters, this article adopts a mechanism modeling method to establish a full system model of intelligent energy meters, in order to analyze the influence of model parameters of each unit on the dynamic errors of active energy, and provide important theoretical reference for further improving the dynamic error characteristics of energy meters. In addition, identifying the sources of errors has important application value for improving the algorithm of energy metering chips, optimizing the overall design of energy meters, and selecting energy meters in dynamic load scenarios for the power sector.